Relato de egressos do curso tecnólogo em gestão de cooperativas da universidade federal do Tocantins. - Silva, Gabriela Iarelli da (Universidade Federal do Tocantins, 2023)
This study aimed to report data on graduates of the Technologist course of Cooperative Management, the Federal University of Tocantins, searching to know: how long formed; which the year of entry to university; where are you living; you are working in their area of training; and finally know where the CST ongoing Cooperative Management contributed to their professional training. Until the semester 2015/1, the total number of trainees in the course of Cooperative Management was 51, only 11 of these answered the open questionnaire sent vi email. Data for the study were known from the academic secretary of the University, which also reported the e-mail contact. The study reports some of the history of Colleges Technology (CST) and the design and pedagogical project of Cooperative Management Course. Brings data technologists courses in cooperative management in Brazil and ends with the reporting data. The data show that the vast most of the respondents do not work in the training area, but intend to in the future, following the profession; that the graduates are satisfied with the profession they have chosen the possibility of adding in working with associations because you can see that the theory expands knowledge, bringing efficiency in the work done.